Morphometric Analysis of Glenoid, Coracoid Process and Scapular Spine in a tertiary care center- 3D CT Study - Dr Mozimul Haq Siddiqui; Dr Prashantha (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Recurrent anterior shoulder instability with glenoid bone loss poses a significant challenge in orthopedic practice. Achieving favourable functional outcomes depends on selecting an appropriate graft type and ensuring its safe fixation on the glenoid. Despite the importance of morphometric data, there is a paucity of studies analyzing the dimensions of the glenoid, coracoid process, and scapular spine in a tertiary care Center. Purpose: To evaluate the morphometric dimensions of the glenoid, coracoid process, and scapular spine in the Indian population, which can guide clinical decisions in managing recurrent anterior shoulder instability. Methods: A total of 3D CT scans of 300 shoulders from 150 patients with non-orthopedic conditions were analyzed. Measurements included: Glenoid: Mean height and width. Coracoid process: Mean height, width, and length of harvestable coracoid. Scapular spine: Mean width and length of harvestable segments. Results: This study highlights important morphometric data on the glenoid, coracoid process, and scapular spine among the Indian population. The results have direct clinical relevance, especially in addressing recurrent anterior shoulder instability with glenoid bone loss. The key findings include: Glenoid Dimensions: Mean height of 34.8 mm and mean width of 24.6 mm. Coracoid Process Dimensions: Mean height of 8.2 mm and 9.3 mm, and mean width of 11.7 mm and 13.1 mm at fixation points. Harvestable coracoid length averaged 21.9 mm. Scapular Spine Dimensions: Mean width of 8.2 mm and 7.7 mm at fixation points, and mean harvestable length of 30.4 mm. Gender Differences: Statistically significant differences in measurements were observed between genders. Conclusions: This morphometric evaluation can guide surgeons in selecting appropriate grafts and fixation techniques tailored to patient anatomy, potentially improving functional outcomes in cases of recurrent shoulder instability.